Synthesized 2nd Generation Zeolite as an Acid-Catalyst for Esterification Reaction - Alfattal, Ali H.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
MCM-48 zeolites have unique properties from the surfaces and structure point of view as it’s shown in the results ,and unique and very sensitive to be prepared, have been experimentally prepared and utilized as a second-generation/ acid - catalyst for esterification reactions of oleic acid as a model oil for a free fatty acid source with Ethanol. The characterization of the catalyst used in the reaction has been identified by various methods indicating the prepared MCM-48 is highly matching the profile of common commercial MCM-48 zeolite. The XRF results show domination of SiO2 on the chemical structure with 99.1% and agreeable with the expected from MCM-48 for it’s of silica-based, and the SEM results show the cubic crystallographic space group compatible with Ia3d space group giving the hexagonal surface structure. The AFM test gave an average particle diameter of 97.51 nm and an average catalyst roughness of 0.855 nm. Esterification reaction of oleic acid with ethanol on MCM-48 has been carried in a batch reactor with 5% the prepared MCM-48 zeolite catalyst loading gives 81% of conversion after one hour at 353K